URGENCY OF SEMANTICS AND SCIENCE APPROACH FOR QUR’ANIC RESEARCH AS ISLAMIZATION STUDY - Irwanto, Irwanto; Al Faruq, Abdul Qudus; Isyak, Isyak; Thobroni, Ahmad Yusam (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2025)
In an era of globalization and modern scientific advancement, aligning scientific methodologies with Islamic principles is crucial to fostering an Islamic scientific paradigm. this research uses descriptive and analyses methods, while the type of research is library research. the purposes of this research are to reveal the position of semantics and Qur'anic science towards the Islamisation of science for its contribution to the civilisation of Islamic ideas. This study result by Semantic theory provides a framework for deeper comprehension of Qur'anic meanings, while the application of Qur'anic science bridges religious teachings with empirical inquiry. Together, these approaches demonstrate Islam's relevance and contributions to contemporary knowledge, particularly in fields such as genetic inheritance, which reflects the enduring harmony between Qur'anic insights and modern science.